Feasibility for Measuring Transverse Area Ratios and Asymmetry of Lumbosacral Region Paraspinal Muscles in Working Dogs Using Computed Tomography - Cain, Bethany; Jones, Jeryl C.; Holásková, Ida; Freeman, Larry; Pierce, Bess (Frontiers in Veterinary Science, 2016)
Objectives: Describe computed tomographic (CT) anatomy of canine lumbosacral paraspinal muscles, a method for measuring paraspinal muscle transverse area ratios and asymmetry using CT, and application of this method in a small sample of working dogs with versus without lumbosacral pain. Methods: Published anatomy references and atlases were reviewed and discrepancies resolved by examination of anatomic specimens and multi-planar reformatted images to describe transverse CT anatomy of lumbosacral region paraspinal muscles. Sixteen Belgian malinois military working dogs were retrospectively recruited and assigned to lumbosacral pain positive versus negative groups based on medical record entries. A single observer unaware of dog group measured CT transverse areas of paraspinal muscles and adjacent vertebral bodies, in triplicate, for L5-S1 vertebral locations. A statistician compared muscle transverse area ratios and asymmetry at each vertebral location between groups. Results: The relative co-efficient of variation for triplicate CT area measurements averaged 2.15% (N=16). Multifidus lumborum (L6-7), psoas/iliopsoas (L5-6, L6-7), and sacrocaudalis dorsalis lateralis (L6-7, L7-S1) transverse area ratios were significantly smaller in dogs with lumbosacral pain (n=11) vs. without lumbosacral pain (n=5) (p< 0.05). Muscle asymmetry values were not significantly greater in dogs with vs. without lumbosacral pain. Clinical relevance: Computed tomographic morphometry of lumbosacral region paraspinal muscles is a feasible objective method for use in future evidence-based research studies in working dogs. Potential future research applications include determining whether decreased paraspinal muscle area ratios and/or increased paraspinal muscle asymmetry could be used as markers for preclinical lumbosacral pain in stoic dogs or risk factors for other injuries in high performance canine athletes; or determining whether core muscle strengthening exercise prescriptions for dogs with lumbosacral pain have an effect on paraspinal muscle area ratios and asymmetry.